Beyond information literacy: Why metaliteracy is crucial for modern health education programs - Fatemeh Zarei; Sridevi Adivi (BioSocial Health Journal)
Metaliteracy is a critical skill that enables individuals to evaluate information for bias, accuracy, and truthfulness, and construct knowledge. The paper argues that metaliteracy is essential in modern health education, and not only information literacy. Metaliteracy enables health educators to critically appraise health information thereby promoting accurate knowledge dissemination. It also enhances the core skills of health educators by allowing them to maneuver through the "infodemic," debunking misinformation and creating usable health advices. By embracing metaliteracy, health education may protect public health and elevates its professional standing.